2010
DOI: 10.17221/87/2009-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of silver fir (Abies alba Mill) growing at the upper limit of its occurrence in the Šumava National Park and Protected Landscape Area

Abstract: AbstRACt:In the second half of 20 th century silver fir regeneration has been observed throughout all of the Europe, including the Czech Republic. The Bohemian Forest -Šumava Mts. is one of the regions where the silver fir percentage in forest stands is supposed to be increased from the present 2% to nearly 12%. During the period 2006-2007, in the Czech part of the Bohemian Forest, samples of silver fir were taken mainly in the upper altitudinal limit of silver fir occurrence. In the present paper the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
3
7
1
Order By: Relevance
“…These values are in the range of nitrogen concentration found by other authours. In Šumava where silver fir has been also reintroduced, N concentration ranged from 0.95% to 2.15% (mean -1.39%) [6]. The concentration in the range of 1.1% to 1.25% were found in Germany and Slovakia [8,9].…”
Section: The Content Of -Micro and -Macro Elements In Leaves And Soilmentioning
confidence: 98%
See 4 more Smart Citations
“…These values are in the range of nitrogen concentration found by other authours. In Šumava where silver fir has been also reintroduced, N concentration ranged from 0.95% to 2.15% (mean -1.39%) [6]. The concentration in the range of 1.1% to 1.25% were found in Germany and Slovakia [8,9].…”
Section: The Content Of -Micro and -Macro Elements In Leaves And Soilmentioning
confidence: 98%
“…It was found that needles taken from weakened firs contain less K than the vital ones [10]. K content in silver fir needles from Bohemian Forest ranged from 0.3% to 1.1% [6]. In other investigations the mean K content in needles varied from 0.6% (Slovakia) to 0.8% (Poland) [9] and in Germany, the mean value in the fir needles was found to be 0.77% [8,11].…”
Section: The Content Of -Micro and -Macro Elements In Leaves And Soilmentioning
confidence: 99%
See 3 more Smart Citations